2021
DOI: 10.1016/j.nicl.2021.102664
|View full text |Cite
|
Sign up to set email alerts
|

Resting state functional connectivity in the default mode network: Relationships between cannabis use, gender, and cognition in adolescents and young adults

Abstract: Highlights We examined resting state connectivity in the DMN in cannabis users and controls. Cannabis users displayed abnormal connectivity compared to healthy controls. Abnormal connectivity in cannabis users related to poorer cognitive performance. Abnormal brain communication may remain after ≥ 3 weeks of cannabis abstinence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 114 publications
2
19
0
Order By: Relevance
“…Previous studies have shown sex differences in neuropsychological functioning in adolescent and young adult cannabis users [ 90 ]. Our results are consistent with prior studies in cannabis using adolescents and adults that have shown alterations in brain structure, activity, and connectivity in cortical and cerebellar regions rich in CB 1 R in women that correlate with cognitive impairments and, in some cases, are directionally opposite from those found in men [ 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 ]. Of note, none of these prior reports identified sex-by-cannabis group differences in the insula, although one [ 98 ] did show higher cerebral blood flow in the insular cortex of males compared to females in both cannabis using and non-using control groups.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have shown sex differences in neuropsychological functioning in adolescent and young adult cannabis users [ 90 ]. Our results are consistent with prior studies in cannabis using adolescents and adults that have shown alterations in brain structure, activity, and connectivity in cortical and cerebellar regions rich in CB 1 R in women that correlate with cognitive impairments and, in some cases, are directionally opposite from those found in men [ 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 ]. Of note, none of these prior reports identified sex-by-cannabis group differences in the insula, although one [ 98 ] did show higher cerebral blood flow in the insular cortex of males compared to females in both cannabis using and non-using control groups.…”
Section: Discussionsupporting
confidence: 92%
“…Repeated use during adolescence may result in alterations in regions rich in eCB signaling, including the parietal cortex [ 10 , 11 , 12 ], a region that continues to develop into adolescence and underlies sustained attention [ 13 ]. Consistent with this, several neuropsychological studies have shown evidence that young regular cannabis users, typically defined as at least weekly cannabis use, have demonstrated poorer sustained and selective attention, attentional control, and increased lapses in attention [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. Thus, repeated exposure to cannabis during the neurodevelopmental phase of adolescence may result in alterations in the attentional network.…”
Section: Introductionmentioning
confidence: 71%
“…There is compelling evidence in preclinical and clinical studies that chronic use of cannabis during adolescence and early adulthood can have detrimental effects on cognitive function and brain structure ( Ritchay et al, 2021 ). In contrast, translational research using healthy-aging, 18–24-month-old mice shows improved cognitive function to very low dose Δ9-THC ( Bilkei-Gorzo et al, 2017 ; Sarne et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%